"One‐Pot" Sample Processing Method for Proteome‐Wide Analysis of Microbial Cells and Spores. Issue 5 (16th April 2018) - Swarge, Bhagyashree Nandakishor; Roseboom, Winfried; Zheng, Linli; Abhyankar, Wishwas R.; Brul, Stanley; de Koster, Chris G.; de Koning, Leo J.
Abstract : Purpose: Bacterial endospores, the transmissible forms of pathogenic bacilli and clostridia, are heterogeneous multilayered structures composed of proteins. These proteins protect the spores against a variety of stresses, thus helping spore survival, and assist in germination, by interacting with the environment to form vegetative cells. Owing to the complexity, insolubility, and dynamic nature of spore proteins, it has been difficult to obtain their comprehensive protein profiles. Experimental design: The intact spores of Bacillus subtilis, Bacillus cereus, and Peptoclostridium difficile and their vegetative counterparts were disrupted by bead beating in 6m urea under reductive conditions. The heterogeneous mixture was then double digested with LysC and trypsin. Next, the peptide mixture was pre‐fractionated with zwitterionic hydrophilic interaction liquid chromatography (ZIC‐HILIC) followed by reverse‐phase LC‐FT‐MS analysis of the fractions. Results: "One‐pot" method is a simple, robust method that yields identification of >1000 proteins with high confidence, across all spore layers from B. subtilis, B. cereus, and P. difficile . Conclusions and medical relevance: This method can be employed for proteome‐wide analysis of non‐spore‐forming as well as spore‐forming pathogens. Analysis of spore protein profile will help to understand the sporulation and germination processes and to distinguish immunogenic protein markers.